Praktek Berbangsa Dan Bernegara Berdasarkan Ketuhanan Di Indonesia Dalam Kaitanya Dengan Teori Pembentukan Negara Teokrasi - Riyanto Riyanto; Avi Firzashafira; Taufiqurrohman Syahuri (Jurnal Hukum dan Sosial Politik, 2024)
Pancasila as a national ideology implies a religious view of the nation, which upholds the values of God Almighty. This is as determined in the constitution of the Republic of Indonesia, which is stated in Article 29 A paragraph (1) of the 1945 Constitution as a result of the amendment of Chapter XI which states that "The state is based on the Almighty God" so that religious legitimacy is still needed in various aspects of the life of the nation and state, so that it cannot be separated from the Theory of Theocracy which states that the supreme power in a country is God's power which means, no one has supreme power in a country, apart from God. The purpose of this study is to examine and analyse carefully the practice of the nation and state based on divinity in Indonesia in relation to the theory of the formation of theocratic states. The legal research method used is normative juridical legal research method by conducting research on library materials and using statute approach. The result of the research is that the practice of religious life should strengthen and strengthen unity, integrity, and national resilience with Pancasila as the state philosophy and ideology of the nation as a determinant of national integration, a source of ethics for state administration, and continue to clarify and reinforce the role of religion as a state direction in the nation and state.